Effect of RNase on Zein Synthesis in Endosperms of brittle-2opaque-2 Maize Double Mutant - Lee, Lisa (1984)
Posttranscriptional degradation of zein mRNAs in Zea mays, presumably caused by high RNase activity, may be involved in reducing zein synthesis in the endosperms of zein-deficient mutants. Zein proteins prepared from mature endosperms of zein-deficient double mutants such as brittle-2;opaque-2 showed an almost complete blockage of the synthesis of two major zein components, Z1 and Z2. However, these two components were present prior to 12 days postpollination. The changes in quantity and quality of zein synthesis in these double mutants correlated well with the rising RNase levels in the developing endosperm. In addition to its effect on zein synthesis, high RNase activity also influenced the stability of rRNAs in the brittle-2;opaque-2 double mutant at the later stages of endosperm development. These results suggest that RNase played a role in regulating zein synthesis in developing zein-deficient mutant endosperms.